2022
DOI: 10.1186/s12860-022-00457-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of lncRNA HOXA-AS2 promotes the progression of oral squamous cell carcinoma by mediating SNX5 expression

Abstract: Background Oral squamous cell carcinoma (OSCC) is one of the most common head and neck cancers. Long non-coding RNA HOXA-AS2 (lncRNA HOXA-AS2) have been extensively studied in various cancers. However, the expression and function of HOXA-AS2 in OSCC still remain unknown. The aim of this study is to investigate the roles of HOXA-AS2 in OSCC. Methods OSCC tissues and adjacent normal tissues were obtained from OSCC patients. RT-qPCR and Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Given that inhibition of autophagy and promotion of apoptosis were conducive to the persistent infection of virus [34], the present data suggested that EcSNX5 had positive regulatory roles on viral infection. In mammals, SNX5 can increase the expression of ERK 1/2 that inhibits autophagy by activating the mTOR signaling pathway [35], suggesting that EcSNX5 may also have unique way of inhibiting autophagy. Additionally, given that autophagy contributes to RGNNV replication [36], these data suggested that EcSNX5 promote virus proliferation by inhibiting autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Given that inhibition of autophagy and promotion of apoptosis were conducive to the persistent infection of virus [34], the present data suggested that EcSNX5 had positive regulatory roles on viral infection. In mammals, SNX5 can increase the expression of ERK 1/2 that inhibits autophagy by activating the mTOR signaling pathway [35], suggesting that EcSNX5 may also have unique way of inhibiting autophagy. Additionally, given that autophagy contributes to RGNNV replication [36], these data suggested that EcSNX5 promote virus proliferation by inhibiting autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In PCa, HOXA-AS2 plays a role in the regulation of cell proliferation, migration, and EMT through the miR-885-5p/KDM5B and miR-509-3p/PBX3 axes [ 165 , 166 ]. Furthermore, in OSCC, HOXA-AS2 promotes tumor progression by modulating CDK8 and SNX5, while suppressing miR-567 and miR-520c-3p, respectively [ 167 , 168 ]. Moreover, HOXA-AS2 acts as a sponge for miR-520c-3p and miR-106a to regulate TGFBR2/RELA and SCN3A, respectively, thereby enhancing tumor progression in BC [ 169 , 170 ].…”
Section: Introductionmentioning
confidence: 99%